Evaluation of the combined toxicity of compound pollutants of azole fungicides to Raphidocelis subcapitata - Huang Yongxiang; Guo Dijie; Qin Litang (E3S Web of Conferences, 2025)
In order to investigate the combined toxicity of compound contaminated azole fungicides on alage. Systematic investigation of Difenoconazole, Penconazole, Metconazole, Tetraconazole, Flutriafol, Fuberidazole, Triflumizole, Terrazole, HyMexazol, 9 azole fungicides as the components of the mixture. Thirty-five binary mixture systems with 173 mixture rays were designed by direct equipartition ray method. The growth inhibition toxicity of binary mixtures to Raphidocelis subcapitata was determined by 96-well microplates. Toxic interactions were qualitatively analyzed by Concentration addition (CA) and Independent Action (IA) models. Model Deviation Ratio (MDR) was used to quantitatively evaluate the toxic interaction of binary mixtures of azole fungicides, as well as the equivalent graph method, Toxic Unit (TU) method, additivity Index method (AI), Toxicity Index (MTI) and Combination Index (CI) methods were used to analyze the combined toxicity and toxic interaction of the mixture. The results showed that the frequency of synergistic effect was higher when mixed with Difenoconazole, Penconazole and Triflumizole, and the binary mixing with Flutriafol, Fuberidazole and Metconazole could reduce the toxicity of the mixture, showing additive and antagonistic effects. The toxicity of the mixture ranged from 3.053 to 6.415. In addition, at ambient concentrations, the mixture interaction is dominated by addition.